2016
DOI: 10.1038/nmicrobiol.2016.108
|View full text |Cite
|
Sign up to set email alerts
|

The binary toxin CDT enhances Clostridium difficile virulence by suppressing protective colonic eosinophilia

Abstract: Clostridium difficile is the most common hospital acquired pathogen in the United States, and infection is in many cases fatal. Toxins A and B are its major virulence factors, but increasingly a third toxin may be present, known as C. difficile transferase (CDT). An ADP-ribosyltransferase that causes actin cytoskeletal disruption, CDT is typically produced by the major, hypervirulent strains and has been associated with more severe disease. Here we show that CDT enhances the virulence of two PCR-ribotype 027 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
159
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 52 publications
6
159
0
2
Order By: Relevance
“…Previous data have found that the patients infected with C. difficile producing CDT had higher fatality rate (approximately 60%) than those infected with CDT-deficient strains [13]. A more recent study found that the binary toxin enhanced two PCR-ribotype 027 strains (R20291 and M7404) in mice by suppressing protective colonic eosinophilia [50]. Sequence comparisons demonstrated that the CdtLoc harbored in the ST201 strains was highly homologous to that of strain R20291, and the three genes cdtA, ctdB and ctdR carried by the ST201 CdtLoc were intact and also highly homologous to their corresponding genes harbored by R20291, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have found that the patients infected with C. difficile producing CDT had higher fatality rate (approximately 60%) than those infected with CDT-deficient strains [13]. A more recent study found that the binary toxin enhanced two PCR-ribotype 027 strains (R20291 and M7404) in mice by suppressing protective colonic eosinophilia [50]. Sequence comparisons demonstrated that the CdtLoc harbored in the ST201 strains was highly homologous to that of strain R20291, and the three genes cdtA, ctdB and ctdR carried by the ST201 CdtLoc were intact and also highly homologous to their corresponding genes harbored by R20291, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This activates a cascade of proinflammatory cytokines such as TNF-α, IL-23, IL-1β, and interferon-γ, leading to apoptosis of gut epithelial cells and increased permeability of the intestinal mucosa, preceding disease worsening and progression. 31, 32 In the active state of IBD, reports have shown that the innate immune system is activated and responds by secreting a host of proinflammatory cytokines such as IL-1β, IL-6, IL-8, and TNF-α, amplifying the inflammatory response and ultimately resulting in tissue damage. 33, 34 In this study, the amounts of TNF-α in the tissue were elevated in the IBD group, but were significantly increased in the CDI and IBD group, which may be associated with the increased severity of the concurrent diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of the ribotype 027 lineage have often been described as “hypervirulent” (11, 15). Studies have pointed to increased toxin production (16), production of a binary toxin (17), fluoroquinolone resistance (14), increased frequency of sporulation (18), enhanced ecological fitness (19) and a higher correlation with recurrent infection (20, 21) as potential mechanisms that led to increased incidence and/or severity of infections associated with ribotype 027 strains. However, some “hypervirulent” attributes of ribotype 027 vary across strains (e.g., degree of toxin production and sporulation (22)) or are found in ribotypes not typically associated with increased disease severity (e.g., fluoroquinolone resistance (23)), making it difficult to pinpoint specific mechanisms responsible for increased incidence and/or severity of infection with ribotype 027 strains.…”
Section: History Of C Difficile Infectionmentioning
confidence: 99%